Modified sawdust concrete/Modifikuotas pjuvenų betonas - Kantautas, Aras; Vaickelionis, Giedrius (Journal of Civil Engineering and Management, 2000)
Wood-cement materials are widely produced and applied in many developed countries. In this case special prepared wood aggregates are employed. Wood sawdust practically is not employed. Extracts, present in wood, slow down the cement hydration. The influence of mineral additives on this process was determined. The efficiency of mineral additives depends on their hydraulic activity. It has been found that the mineral components (additives) of sawdust concrete have a positive effect on cement setting and hardening due to two reasons: 1) hydraulic and other mineral additives absorb wood extracts from liquid phase which inhibit and retard setting of cement and reduce their concentration in solution; 2) reduce pH of liquid phase so the hemicellulose which is in sawdust or other wood aggregates, less disintegrate lightly soluable sugars. When sawdust amounts are different, the optimum cement and rottenstone relation is not constant: y = 1,29x −0,66 , where y is cement and rottenstone mass relation, x is sawdust and binding material (cement+rottenstone) volume relation. The influence of sawdust concrete humidity on its strength was found: where y is concrete compressive strength (MPa), when its humidity X (%), R is concrete compressive strength (MPa), when its humidity W(%). The possibility of accelerating the hardening process of concrete mixes of cement-rottenstone (gaize)-sawdust system by means of steaming at 80 °C was studied, too. It is impossible when producing ordinary wood-cement materials. The physical and technical properties of sawdust concrete such as shrinkage strain, expansion deformations and elastic modulus were determined. Sawdust concrete contraction deformation depending on concrete density may vary by 8…14 mm/m and expansion (in humid conditions) by 1,1…2,5 mm/m. Deformation decreases when quartz sand additive is used. When the concrete gets dry repeatedly, deformations are smaller. The sawdust concrete elasticity modulus is similar to that of light concrete with inorganic additives having the same density. Its frost resistance depends on the concrete structure and cement quantity. When the concrete with a small amount of sawdust is used (cement+additive: sawdust = 5:1), the samples endure 75 freezing cycles. The heat conductivity of sawdust concrete is low. The experimental data have shown that structural thermoinsulated small blocks can be produced from these concrete mixes. Article in Lithuanian. First Published Online: 26 Jul 2012